Comparison of prophylactic clip and endoloop application for the prevention of postpolypectomy bleeding in pedunculated colonic polyps: a prospective, randomized, multicenter study - Ji, Jeong-Seon; Lee, Seung-Woo; Kim, Tae Ho; Cho, Young-Seok; Kim, Hyung-Keun; Lee, Kang-Moon; Kim, Sang-Woo; Choi, Hwang (Endoscopy, 2014)
Background and study aims: The effectiveness of the prophylactic clip for the prevention of postpolypectomy bleeding in pedunculated colonic polyps has not been confirmed. The aim of this prospective, randomized study was to compare the efficacy of prophylactic clip and endoloop application in the prevention of postpolypectomy bleeding in large pedunculated polyps.Patients and methods: A total of 195 patients who had pedunculated colorectal polyps, with heads ≥ 10 mm and stalks ≥ 5 mm in diameter, were included in the study between July 2010 and January 2013. Polyps were randomized to receive either clips or endoloops. Both devices were applied to the base of the stalk before conventional snare polypectomy. Bleeding complications were analyzed with a noninferiority margin of 5 %.Results: A total of 203 polyps were included in the study (98 in the clip group and 105 in the endoloop group). Bleeding occurred after five polypectomies in the clip group (5.1 %) and after six in the endoloop group (5.7 %) (P = 0.847). Noninferiority of the prophylactic clip to the endoloop could not be confirmed (absolute bleeding rate difference – 0.6 %, 95 % confidence interval – 5.6 % to 6.8 %) due to small sample size. Immediate bleeding episodes occurred in 4/5 polyps in the clip group and 5/6 polyps in the endoloop group. Delayed bleeding occurred in one polyp in each group.Conclusions: These results suggest that the application of a prophylactic clip is as effective and safe as an endoloop in the prevention of postpolypectomy bleeding in large pedunculated colonic polyps. Clinical trial registration: ClinicalTrials.gov (NCT01406379)